Effectiveness of Interactive and Independent Instructional Strategies as Perceived by Business Studies Teachers in Secondary Schools in Anambra State - Okorafor, Anthony Osinachi; Anazor, Tochukwu Vivien (Journal of Research in Industrial Technology and Educational Studies, 2025)
This study sought to find out the effectiveness of interactive and independent instructional strategies as perceived by business studies teachers in secondary schools in Anambra state. Two research questions and two null hypotheses guided the conduct of this study. The research design was descriptive survey. The population of this study consisted of 283 business studies teachers in pubic secondary schools in Anambra state. The entire population was used for the study without sampling.  The instrument for data collection was a structured questionnaire. The questionnaire was tested for validity and reliability using Cronbach’s alpha method, the overall reliability coefficient was 0.87. Descriptive and inferential statistics was used for data analysis. Specifically, mean was used in answering the research questions while standard deviation was used to determine the homogeneity of the respondents’ ratings. The null hypotheses were tested using two-way ANOVA. The probability alpha level for rejecting or accepting the null hypotheses was set at 0.05 level of significance. Findings from the study revealed that business studies teachers in secondary schools in Anambra State perceived interactive instructional strategy as fairly effective and independent instructional strategy as effective. The findings also revealed that gender was not a significant factor in the teachers' perception of the effectiveness of the instructional strategies. Based on the findings, it was recommended among others that interactive instructional strategies which was adjudged to be fairly effective is recommended for compulsory application in teaching business studies in secondary schools in Anambra state. This frame work would enable the students to acquire the necessary skills for paid or self-employment and that teachers should continue and constantly use independent teaching strategy as the approach influences students’ activeness in the process of learning and fosters good performance.
Keywords: Effectiveness; interactive; independent; instructional strategies; business studies